Solid damping material for passive tension viscous damper and preparation method of solid damping material
The limited frequency response range of traditional damping materials is solved by using a combination of polymer matrix, reinforcement materials, plasticizers, crosslinkers, microencapsulated self-repairing agents and modified nanoclays in passive tension viscous dampers. The memory effect problem achieves wider frequency response and more stable dynamic performance.
Patent Information
- Application Number
- CN202411824936.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-14
Smart Images

Figure CN119432044A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of damper damping materials, and in particular to a solid damping material for a passive tension viscous damper and a preparation method thereof. Background Art
[0002] Passive tension viscous damper is a device used for structural vibration reduction, which is widely used in the vibration reduction of large structures such as buildings and bridges. Its core principle is to use the internal friction characteristics of the damping material to reduce the vibration response of the structure by converting the vibration energy into heat energy. The choice of damping material directly affects the performance of the damper, including its damping capacity, temperature adaptability, durability and maintenance cost.
[0003] However, the solid damping materials used in traditional passive tension viscous dampers still have the following shortcomings: (1) Limited frequency response: Solid damping materials work well within a specific frequency range, but may not perform well over a wider frequency range. This limits the application of solid damping materials in vibrations of different types and frequencies.
[0004] (2) Memory effect: Solid damping materials have a memory effect, that is, the stress-strain curves of the material during loading and unloading do not overlap, showing a lagging historical dependence. This effect may lead to complex dynamic responses and affect the expected performance of the design.
[0005] Currently, no effective solution has been proposed for the problems in the related technologies. Summary of the invention
[0006] In view of the problems in the related art, the present invention proposes a solid damping material for a passive tension viscous damper and a preparation method thereof to overcome the above technical problems existing in the existing related art.
[0007] To this end, the specific technical solution adopted by the present invention is as follows: According to one aspect of the present invention, a solid damping material for a passive tension viscous damper is provided, wherein the solid damping material for a passive tension viscous damper comprises the following components in mass fractions: 60-70 parts of polymer matrix; 8-12 parts of reinforcement material; 3-5 parts of plasticizer; 1-2 parts of cross-linking agent; 5-10 parts of microencapsulated self-healing agent; 3-8 parts of modified nano clay.
[0008] Furthermore, the polymer matrix includes at least one of thermoplastic polyurethane elastomer, polyvinyl acetal, thermoplastic rubber, ethylene-vinyl acetate copolymer, silicone rubber, polycarbonate and epoxy resin.
[0009] Among them, thermoplastic polyurethane elastomer is a material with excellent elasticity and wear resistance, which is suitable as the matrix of damping material.
[0010] Polyvinyl acetal has excellent transparency and viscoelasticity and can be used in applications requiring high damping and flexibility, and is suitable for damping materials that require transparency or biocompatibility.
[0011] Thermoplastic rubber combines the properties of thermoplastics and rubber, is easy to process, has good flexibility and weather resistance, and is widely used in automotive parts, seals, shock absorbers and other fields.
[0012] Ethylene-vinyl acetate copolymer has excellent softness, impact resistance and aging resistance, and is often used in soles, cushioning materials and sports equipment.
[0013] Silicone rubber has excellent high and low temperature resistance and chemical stability, and has excellent elasticity, making it suitable for high temperature environments or applications requiring high chemical resistance.
[0014] Polycarbonate has high strength and toughness, high transparency and good heat resistance, and is suitable for structural parts that require high strength and transparency.
[0015] Epoxies have excellent mechanical properties, bond strength and electrical insulation properties and are suitable for applications requiring high strength and chemical resistance.
[0016] Furthermore, the reinforcing material includes carbon nanotubes and graphene oxide, and the ratio of the carbon nanotubes to the graphene oxide is in the range of 2:1-3:1.
[0017] Carbon nanotubes provide excellent mechanical strength and thermal conductivity, and increase the material's toughness and impact resistance.
[0018] Graphene oxide provides excellent interface interactions, which helps to improve the comprehensive mechanical properties of the material, improve the thermal conductivity and dimensional stability of the material, and reduce the memory effect.
[0019] Furthermore, the plasticizer includes at least one of di(2-ethylhexyl)phthalate, diisononyl phthalate, dicyclohexyl phthalate, acetylcitrate tributyl and dioctyl adipate.
[0020] Di(2-ethylhexyl) phthalate (DEHP), used to increase the flexibility of the polymer and help adjust the damping properties.
[0021] Diisononyl phthalate (DINP) has lower volatility and better durability than DEHP and is often used in applications requiring long-term flexibility and low migration.
[0022] Dicyclohexyl phthalate (DINCH) does not contain phthalates, has good biocompatibility and low toxicity, and is suitable for applications with high safety requirements such as medical devices and children's toys.
[0023] Acetyl tributyl citrate (ATBC) is a non-toxic bio-based plasticizer with good biodegradability and compatibility.
[0024] Dioctyl adipate (DOA) provides excellent low temperature flexibility, making it suitable for applications in low temperature environments.
[0025] Furthermore, the cross-linking agent includes at least one of dicumyl peroxide, benzoyl peroxide and azobisisobutyronitrile.
[0026] Dicumyl peroxide improves the material's heat resistance and elastic recovery through chemical cross-linking.
[0027] Benzoyl peroxide is a commonly used free radical initiator with good crosslinking ability and relatively low decomposition temperature, and is suitable for the crosslinking of a variety of polymers.
[0028] Azobisisobutyronitrile is a free radical initiator that produces nitrogen gas upon thermal decomposition, which helps to form the foam structure and improves the strength and heat resistance of the material.
[0029] Furthermore, the microencapsulated self-healing agent is used to be distributed in the damping material matrix and trigger the self-healing process of the solid damping material under different working conditions; The preparation of the microencapsulated self-repairing agent comprises: A self-healing agent is prepared, and a microcapsule wall material is selected according to the chemical properties of the self-healing agent and the expected triggering mechanism, wherein the self-healing agent includes epoxy resin and polyurethane, and the microcapsule wall material includes a mechanical stress-triggered microcapsule wall material and a temperature-triggered microcapsule wall material; The mechanical stress-triggered microcapsule wall material and the temperature-triggered microcapsule wall material are respectively stirred with the self-healing agent, and an emulsifier is added to form a corresponding mixed emulsion; Adding a microcapsule wall material crosslinking agent into the mixed emulsion allows the microcapsule wall material to polymerize at the emulsion interface to form a microcapsule shell layer. By controlling the key variables of the interfacial polymerization reaction, the desired microcapsule thickness and strength can be obtained. Stop the reaction, filter, wash and dry the microcapsules to obtain corresponding mechanical stress-triggered microcapsules and temperature-triggered microcapsules; Wherein, the mechanical stress-triggered microcapsule wall material comprises at least one of a brittle polymer and a polyacrylate; The temperature-triggered microcapsule wall material includes at least one of a thermosensitive polymer, a thermoplastic polymer and paraffin.
[0030] Further, the key variables of the interfacial polymerization reaction to obtain the desired microcapsule thickness and strength include: Determine the key variables that affect microcapsule formation, including reaction temperature, reaction time, microcapsule wall material crosslinking agent concentration, emulsifier concentration, and stirring speed; The chemical reaction and material transfer in the interfacial polymerization process are simulated by modeling; the reaction conditions are optimized using numerical optimization techniques to find the optimal key variables; According to the optimization results, the key variables of the required microcapsule thickness and strength are obtained, and based on the key variables of the required microcapsule thickness and strength, the interfacial polymerization reaction of the microcapsule shell is realized to obtain the required microcapsule thickness and strength.
[0031] Further, the preparation of modified nanoclay includes: The nanoclay is purified by washing and centrifugation, and responsive functional groups are introduced into the surface of the nanoclay by chemical grafting, wherein the responsive functional groups include thermosensitive groups, pH-sensitive groups and photosensitive groups; Intercalants are used to adjust the interlayer spacing of nanoclay; pre-designed templates are used to guide the arrangement of nanoclay particles, and directional distribution of nanoclay is achieved through layer-by-layer self-assembly technology.
[0032] Further, introducing responsive functional groups into the surface of nanoclay includes: Prepare monomers containing thermosensitive groups, monomers containing pH-sensitive groups, monomers containing photosensitive groups and free radical initiators; Nanoclay, a monomer containing a thermosensitive group, a monomer containing a pH-sensitive group, a monomer containing a photosensitive group, and a free radical initiator are mixed in a reaction system; The polymerization reaction is initiated by heating the reaction system to obtain nano clay grafted with responsive functional groups.
[0033] According to another aspect of the present invention, there is also provided a method for preparing a solid damping material for a passive tension viscous damper, the method comprising the following steps: Weighing various raw materials according to the proportions to obtain a polymer matrix, a reinforcing material, a plasticizer, a cross-linking agent, a microencapsulated self-healing agent and modified nanoclay; The modified nanoclay is dispersed in a solvent, and the modified nanoclay is dispersed using ultrasonic technology to obtain a nanoclay solution; the nanoclay solution is mixed with a polymer matrix solution, and the solvent is evaporated after stirring to obtain an intercalated composite material; Taking part of the intercalation composite material, adding part of the reinforcing material, the plasticizer, the cross-linking agent and all of the mechanical stress-triggered microcapsules, and mixing them using a high shear mixer to obtain a solid damping outer layer material; Taking another part of the intercalation composite material, adding another part of the reinforcing material, the plasticizer, the cross-linking agent and all the temperature-triggered microcapsules, and mixing them using a high shear mixer to obtain a solid damping inner layer material; The solid damping inner layer material is placed in a mold and pressed into shape; the solid damping outer layer material is covered on the solid damping inner layer material, pressed into shape again, and after curing treatment, a solid damping material is obtained.
[0034] The beneficial effects of the present invention are: (1) The frequency response range of the composites is significantly extended by using different types of reinforcement materials and functionalized modified nanoclays. The high thermal and electrical conductivity of these composites can efficiently absorb and dissipate vibration energy over a wider frequency range.
[0035] (2) Through the microencapsulated self-healing agent, the material can repair itself when damaged, reducing the historical dependence caused by the memory effect. The self-healing process can restore the original shape and performance of the material. The use of cross-linking agents helps to form a more stable three-dimensional network structure, reducing the hysteresis effect caused by strain history.
[0036] (3) The use of modified nanoclay improves the mechanical strength and thermal stability of the material, and the introduction of responsive functional groups gives the material adaptability under different environmental conditions. In addition to enhancing the mechanical properties, the use of carbon nanotubes and graphene oxide also improves the durability and environmental aging resistance of the material.
[0037] (4) Mechanical stress-triggered microcapsules can automatically rupture when the material is subjected to external mechanical damage (such as scratches and cracks), release internal self-healing agents, fill the damaged area, significantly extend the service life of the material, and reduce maintenance work. Temperature-triggered microcapsules rupture or increase permeability when the ambient temperature changes or the temperature inside the material rises to a certain level, and release self-healing agents, which also help repair material deformation or damage caused by temperature. The combination of mechanical stress triggering and temperature triggering enables the material to respond automatically under a variety of environmental conditions, improving the adaptability of the material in dynamic environments.
[0038] (5) The present invention customizes microcapsules to suit specific applications. By adjusting the reaction conditions (such as temperature, time, emulsifier and cross-linker concentrations), the properties of the microcapsules can be customized to adapt to different mechanical or thermal environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 The present invention is a flowchart of a method for preparing a solid damping material for a passive tension viscous damper according to an embodiment of the present invention. DETAILED DESCRIPTION
[0041] To further illustrate each embodiment, the present invention provides drawings, which are part of the disclosure of the present invention and are mainly used to illustrate the embodiments and can be used in conjunction with the relevant descriptions in the specification to explain the operating principles of the embodiments. With reference to these contents, ordinary technicians in the field should be able to understand other possible implementations and advantages of the present invention. The components in the figures are not drawn to scale, and similar component symbols are generally used to represent similar components.
[0042] According to an embodiment of the present invention, a solid damping material for a passive tension viscous damper and a preparation method thereof are provided.
[0043] The present invention is further described in conjunction with the accompanying drawings and specific embodiments. According to one embodiment of the present invention, a solid damping material for a passive tension viscous damper is provided. The solid damping material for a passive tension viscous damper includes the following components in mass fractions: 60-70 parts of polymer matrix; 8-12 parts of reinforcement material; 3-5 parts of plasticizer; 1-2 parts of cross-linking agent; 5-10 parts of microencapsulated self-healing agent; 3-8 parts of modified nano clay.
[0044] In one embodiment, the polymer matrix includes at least one of thermoplastic polyurethane elastomer, polyvinyl acetal, thermoplastic rubber, ethylene-vinyl acetate copolymer, silicone rubber, polycarbonate and epoxy resin. The polymer matrix is the main structural component of the solid damping material, which determines the basic mechanical properties of the solid damping material, such as strength, hardness and elastic modulus. According to different environmental conditions (such as temperature, humidity, chemical corrosion, etc.) in the application field, a suitable polymer matrix is selected to ensure stable performance of the material. For example, silicone rubber is used for high temperature applications, while polycarbonate is suitable for applications requiring high impact strength.
[0045] In one embodiment, the reinforcing material includes carbon nanotubes and graphene oxide, and the ratio of the carbon nanotubes to the graphene oxide is in the range of 2:1-3:1.
[0046] It should be noted that carbon nanotubes are nanotube-like materials with a high aspect ratio that are rolled up from graphite sheets. They are divided into single-walled carbon nanotubes and multi-walled carbon nanotubes. Graphene oxide is graphene prepared by oxidation treatment, and its surface is rich in oxygen functional groups (hydroxyl, carboxyl, etc.), which makes it have good hydrophilicity and chemical activity. Graphene oxide retains some of the strength and conductivity of graphene, and its oxidized surface structure makes it easy to disperse in a variety of solvents and polymer matrices. By adjusting the ratio of carbon nanotubes to graphene oxide (such as 2:1 to 3:1), the synergistic effect between different reinforcement materials can be achieved and the overall performance of the material can be optimized. Carbon nanotubes provide high-strength support, while graphene oxide provides dispersibility and interface compatibility. The combination of the two improves the comprehensive performance of the material.
[0047] In addition, due to their extremely high elastic modulus, the reinforcing materials (carbon nanotubes and graphene oxide) can change the intrinsic properties of solid damping materials, improve the rigidity and strength of the materials, improve the energy dissipation capacity, prevent or delay the formation and propagation of microcracks, and enhance the dynamic stiffness of the materials, so that the materials can better absorb and transmit vibration energy. By increasing the dynamic stiffness and damping of the materials, the materials can better adapt to vibrations of different frequencies, thereby broadening their frequency response range.
[0048] In one embodiment, the plasticizer includes at least one of di(2-ethylhexyl)phthalate, diisononyl phthalate, dicyclohexyl phthalate, tributyl acetylcitrate, and dioctyl adipate. Plasticizers are additives used to increase the flexibility and processing properties of polymer materials. They reduce the glass transition temperature of polymers through physical interactions with polymer chains, making the materials softer and easier to process. The functions of plasticizers include: improving flexibility and ductility, reducing the glass transition temperature, improving processing properties, adjusting physical and mechanical properties, and enhancing durability and stability.
[0049] The crosslinking agent includes at least one of dicumyl peroxide, benzoyl peroxide and azobisisobutyronitrile. The crosslinking agent can improve the thermal stability of the damping material, enhance the mechanical properties, improve the chemical resistance and control the rheological properties of the material.
[0050] Crosslinking agents have a significant impact on the shape memory effect (SMP) of materials because the crosslinking structure is one of the key factors in achieving the memory effect. Crosslinking forms stable chemical bonds between polymer chains. This network structure helps the material return to its original shape after the external force is removed, thereby achieving the shape memory effect.
[0051] In one embodiment, a microencapsulated self-healing agent is used to be distributed in a damping material matrix and trigger the self-healing process of the solid damping material under different working conditions (e.g., vibration, impact); The preparation of microencapsulated self-healing agent includes: Configure the self-healing agent. Epoxy resin and polyurethane have excellent adhesion and mechanical properties as self-healing agents. Epoxy resin forms a hard solid structure after curing, which is suitable for repairing cracks and defects. Polyurethane provides good flexibility and elasticity, which helps to restore the overall performance of the material. The microcapsule wall material is selected according to the chemical properties of the self-healing agent and the expected triggering mechanism. Microcapsule wall materials include mechanical stress triggered microcapsule wall materials and temperature triggered microcapsule wall materials.
[0052] The mechanical stress triggered microcapsule wall material and the temperature triggered microcapsule wall material are stirred with the self-healing agent respectively, and an emulsifier is added to promote the mixing of the oil and water phases through the action of the emulsifier to form a corresponding mixed emulsion.
[0053] A microcapsule wall material crosslinking agent is added to the mixed emulsion to polymerize the microcapsule wall material at the emulsion interface to form a microcapsule shell layer. The desired microcapsule thickness and strength can be obtained by controlling the key variables of the interfacial polymerization reaction.
[0054] Stop the reaction, filter, wash and dry the microcapsules to obtain corresponding mechanical stress-triggered microcapsules and temperature-triggered microcapsules; specifically, after stopping the reaction, the microcapsules need to be filtered, washed and dried to remove unreacted materials and impurities to obtain pure mechanical stress-triggered microcapsules and temperature-triggered microcapsules.
[0055] The mechanical stress-triggered microcapsule wall material includes at least one of a brittle polymer and a polyacrylate; the brittle polymer can be easily broken when subjected to external forces (such as vibration and impact), thereby releasing the internal self-healing agent. Polyacrylate exhibits good brittle fracture characteristics under mechanical stress and is suitable for use as a stress-triggered microcapsule wall material.
[0056] The wall material of the temperature-triggered microcapsule includes at least one of a thermosensitive polymer, a thermoplastic polymer and paraffin wax; the thermosensitive polymer undergoes physical or chemical changes at a specific temperature to release the contents. Thermoplastic polymers have reversible softening and hardening properties and can release self-healing agents when the temperature changes. Paraffin wax can melt within a specific temperature range to release the internal self-healing agent, and is suitable for environments with drastic temperature changes.
[0057] By distributing microencapsulated self-healing agents in composite materials, the materials can be automatically released to fill the damage and restore the structural integrity of the materials when they are damaged (such as cracks or scratches). Using microcapsules with different triggering mechanisms, the materials can maintain self-healing capabilities under various environmental conditions (such as high mechanical stress or temperature changes) and extend their service life. Microencapsulated self-healing agents significantly enhance the memory effect of solid damping materials by providing a continuous self-healing ability, allowing them to maintain stable performance over multiple uses.
[0058] In one embodiment, key variables of the interfacial polymerization reaction are controlled to obtain the desired microcapsule thickness and strength including: The key variables affecting the formation of microcapsules were determined, including reaction temperature, reaction time, concentration of microcapsule wall material crosslinking agent, emulsifier concentration and stirring speed.
[0059] The chemical reaction and material transfer in the interfacial polymerization process are simulated by modeling. The reaction conditions are optimized using numerical optimization techniques to find the optimal key variables, such as response surface method or genetic algorithm, to optimize the model and find the best combination of reaction conditions.
[0060] According to the optimization results, the key variables of the required microcapsule thickness and strength are obtained, and based on the key variables of the required microcapsule thickness and strength, the interfacial polymerization reaction of the microcapsule shell is realized to obtain the required microcapsule thickness and strength. The thickness and strength of the microcapsule are verified using a microscope or other analytical techniques to ensure that they meet the design requirements. If they do not meet the requirements, the reaction conditions need to be adjusted for further optimization.
[0061] In one embodiment, the preparation of modified nanoclay comprises: The initial nanoclay contains impurities and unreacted products. The nanoclay is purified by washing and centrifugation, and responsive functional groups are introduced into the surface of the nanoclay by chemical grafting. The responsive functional groups include thermosensitive groups, pH sensitive groups and photosensitive groups.
[0062] Among them, the thermosensitive group: for example, N-isopropylacrylamide, is used to prepare materials that can reversibly swell under specific temperature changes.
[0063] pH sensitive groups: For example, acrylic acid or methacrylic acid can adjust the solubility and swelling properties of the material when the pH changes.
[0064] Photosensitive groups: For example, the photoresponsive properties of azobenzene-containing monomers can be used to make light-controllable materials.
[0065] Use intercalants to adjust the interlayer spacing of nanoclay and improve the dispersibility of nanoclay in the polymer matrix; use pre-designed templates to guide the arrangement of nanoclay particles, for example, use microporous membranes or polymer templates of specific shapes to guide the stacking and arrangement of nanoclay. The directional distribution of nanoclay is achieved through layer-by-layer self-assembly technology. Layer-by-layer self-assembly technology is to stack nanoclay layer by layer through methods such as electrostatic attraction or chemical bonding to form a directional structure. This technology can accurately control the thickness and arrangement direction of nanoclay and improve the mechanical properties and functionality of the material.
[0066] By modifying nanoclay, the microstructure, interface characteristics and dynamic performance of solid damping materials are improved, and the frequency response range of the materials is significantly expanded.
[0067] In one embodiment, introducing responsive functional groups into the surface of the nanoclay comprises: A monomer containing a thermosensitive group, a monomer containing a pH sensitive group, a monomer containing a photosensitive group and a free radical initiator are configured.
[0068] Nano clay, monomers containing heat-sensitive groups, monomers containing pH-sensitive groups, monomers containing photosensitive groups and free radical initiators are mixed in a reaction system.
[0069] The polymerization reaction is initiated by heating the reaction system to obtain nano clay grafted with responsive functional groups.
[0070] Embodiment 1 A solid damping material for a passive tension viscous damper, the solid damping material for a passive tension viscous damper comprising the following components in mass fractions: Polymer matrix 60g; Reinforcement material 8g; Plasticizer 3g; Cross-linking agent 1g; 5g of microencapsulated self-healing agent; Modified nanoclay 3g.
[0071] The polymer matrix is a thermoplastic polyurethane elastomer.
[0072] The reinforcing material includes carbon nanotubes and graphene oxide, and the ratio of the carbon nanotubes to the graphene oxide is in the range of 2:1.
[0073] The plasticizer is di(2-ethylhexyl)phthalate.
[0074] The crosslinking agent is dicumyl peroxide.
[0075] Microencapsulated self-healing agents include mechanical stress-triggered microcapsules and temperature-triggered microcapsules.
[0076] The raw materials with the above mass fractions are selected, and the solid damping material for the passive tension viscous damper is prepared according to a method for preparing the solid damping material for the passive tension viscous damper.
[0077] Embodiment 2 A solid damping material for a passive tension viscous damper, the solid damping material for a passive tension viscous damper comprising the following components in mass fractions: Polymer matrix 65g; Reinforcement material 10g; Plasticizer 4g; Cross-linking agent 1.5 g; Microencapsulated self-healing agent 7.5g; Modified nanoclay 5.5g.
[0078] The polymer matrix is a thermoplastic polyurethane elastomer.
[0079] The reinforcing material includes carbon nanotubes and graphene oxide, and the ratio of the carbon nanotubes to the graphene oxide is in the range of 2:1.
[0080] The plasticizer is di(2-ethylhexyl)phthalate.
[0081] The crosslinking agent is dicumyl peroxide.
[0082] Microencapsulated self-healing agents include mechanical stress-triggered microcapsules and temperature-triggered microcapsules.
[0083] The raw materials with the above mass fractions are selected, and the solid damping material for the passive tension viscous damper is prepared according to a method for preparing the solid damping material for the passive tension viscous damper.
[0084] Embodiment 3 A solid damping material for a passive tension viscous damper, the solid damping material for a passive tension viscous damper comprising the following components in mass fractions: Polymer matrix 70g; Reinforcement material 12g; Plasticizer 5g; Cross-linking agent 2g; Microencapsulated self-healing agent 10g; Modified nanoclay 8g.
[0085] The polymer matrix is a thermoplastic polyurethane elastomer.
[0086] The reinforcing material includes carbon nanotubes and graphene oxide, and the ratio of the carbon nanotubes to the graphene oxide is in the range of 2:1.
[0087] The plasticizer is di(2-ethylhexyl)phthalate.
[0088] The crosslinking agent is dicumyl peroxide.
[0089] Microencapsulated self-healing agents include mechanical stress-triggered microcapsules and temperature-triggered microcapsules.
[0090] The raw materials with the above mass fractions are selected, and the solid damping material for the passive tension viscous damper is prepared according to a method for preparing the solid damping material for the passive tension viscous damper.
[0091] Comparative Example 1 A solid damping material for a passive tension viscous damper, the solid damping material for a passive tension viscous damper comprising the following components in mass fractions: Polymer matrix 70g; Reinforcement material 12g; Plasticizer 5g; Cross-linking agent 2g; Microencapsulated self-healing agent 10g.
[0092] The polymer matrix is a thermoplastic polyurethane elastomer.
[0093] The reinforcing material includes carbon nanotubes and graphene oxide, and the ratio of the carbon nanotubes to the graphene oxide is in the range of 2:1.
[0094] The plasticizer is di(2-ethylhexyl)phthalate.
[0095] The crosslinking agent is dicumyl peroxide.
[0096] Microencapsulated self-healing agents include mechanical stress-triggered microcapsules and temperature-triggered microcapsules.
[0097] The raw materials with the above mass fractions are selected, and the solid damping material for the passive tension viscous damper is prepared according to a method for preparing the solid damping material for the passive tension viscous damper.
[0098] Comparative Example 2 A solid damping material for a passive tension viscous damper, the solid damping material for a passive tension viscous damper comprising the following components in mass fractions: Polymer matrix 70g; Reinforcement material 12g; Plasticizer 5g; Cross-linking agent 2g.
[0099] The polymer matrix is a thermoplastic polyurethane elastomer.
[0100] The reinforcing material includes carbon nanotubes and graphene oxide, and the ratio of the carbon nanotubes to the graphene oxide is in the range of 2:1.
[0101] The plasticizer is di(2-ethylhexyl)phthalate.
[0102] The crosslinking agent is dicumyl peroxide.
[0103] The raw materials with the above mass fractions are selected, and the solid damping material for the passive tension viscous damper is prepared according to a method for preparing the solid damping material for the passive tension viscous damper.
[0104] Comparative Example 3 A solid damping material for a passive tension viscous damper, the solid damping material for a passive tension viscous damper comprising the following components in mass fractions: Polymer matrix 70g; Reinforcement material 12g; Plasticizer 5g.
[0105] The polymer matrix is a thermoplastic polyurethane elastomer.
[0106] The reinforcing material includes carbon nanotubes and graphene oxide, and the ratio of the carbon nanotubes to the graphene oxide is in the range of 2:1.
[0107] The plasticizer is di(2-ethylhexyl)phthalate.
[0108] The raw materials with the above mass fractions are selected, and the solid damping material for the passive tension viscous damper is prepared according to a method for preparing the solid damping material for the passive tension viscous damper.
[0109] Experimental example The embodiments 1 to 3 and the comparative examples 1 to 3 were placed in the same test environment for performance testing, that is, the vibration frequency range, memory effect area and hysteresis shape improvement of the effective damping of different solid damping materials were tested. The test results and performance parameters are shown in Table 1: Table 1 Frequency response and memory effect performance test results It can be seen from Table 1 that the solid damping material for the passive tension viscous damper of the present invention has significant improvements in frequency response and memory effect by introducing modified nanomaterials and microencapsulated self-healing agents.
[0110] The materials of Examples 1 to 3 show significant advantages in frequency response range, covering a wider frequency range, while the frequency response ranges of Comparative Examples 1 to 3 are relatively narrow.
[0111] Examples 1 to 3 show significant improvements in memory effect area, indicating that these materials have less stress-strain hysteresis during loading and unloading. This indicates that the material can recover to the initial state faster, reducing history dependence and improving the linearity of dynamic response. The memory effect area of the comparative sample is larger, indicating that the material has more significant hysteresis effect under stress conditions and poor dynamic response.
[0112] The hysteresis shapes of Examples 1 to 3 were "significantly" improved, which means that the stress-strain curve of the material after being subjected to force is closer to the ideal elastic behavior, showing excellent dynamic performance. Although Comparative Example 1 also showed significant improvement, the effect was not as good as that of Examples 1 to 3, and Comparative Examples 2 and 3 did not show significant improvement in the hysteresis shape.
[0113] The solid damping material for a passive tension viscous damper provided by the present invention has great application potential, can provide effective shock absorption effect under a wider range of vibration conditions, maintain stable performance during long-term use, and reduce maintenance costs.
[0114] like Figure 1 According to another embodiment of the present invention, there is also provided a method for preparing a solid damping material for a passive tension viscous damper, the method comprising the following steps: S1. Weigh the raw materials according to the proportion to obtain a polymer matrix, a reinforcing material, a plasticizer, a cross-linking agent, a microencapsulated self-healing agent and modified nanoclay.
[0115] S2. Dispersing the modified nanoclay in a solvent, using ultrasonic technology to disperse the modified nanoclay to obtain a nanoclay solution; mixing the nanoclay solution with a polymer matrix solution, stirring evenly, and then evaporating the solvent to obtain an intercalated composite material.
[0116] S3. Take part of the intercalated composite material, add part of the reinforcing material, plasticizer, cross-linking agent and all the mechanical stress-triggered microcapsules, mix them using a high shear mixer, and obtain a solid damping outer layer material.
[0117] S4. Take another part of the intercalation composite material, add another part of the reinforcing material, the plasticizer, the cross-linking agent and all the temperature-triggered microcapsules, mix them using a high shear mixer, and obtain a solid damping inner layer material.
[0118] S5, placing the solid damping inner layer material into a mold and pressing it into shape; covering the solid damping outer layer material on the solid damping inner layer material, pressing it into shape again, and obtaining the solid damping material after curing treatment.
[0119] In summary, the frequency response range of the composite material is significantly expanded by using different types of reinforcing materials and functionalized modified nanoclays. The high thermal conductivity and electrical conductivity of these composite materials can efficiently absorb and dissipate vibration energy in a wider frequency range. Through the microencapsulated self-healing agent, the material can spontaneously repair when damaged, reducing the historical dependence caused by the memory effect. The self-healing process can restore the original shape and performance of the material. The use of cross-linking agents helps to form a more stable three-dimensional network structure and reduces the hysteresis effect caused by strain history. The use of modified nanoclay improves the mechanical strength and thermal stability of the material, and the introduction of responsive functional groups gives the material adaptability under different environmental conditions. In addition to enhancing the mechanical properties, the use of carbon nanotubes and graphene oxide also improves the durability and environmental aging resistance of the material. Mechanical stress-triggered microcapsules can automatically rupture when the material is subjected to external mechanical damage (such as scratches and cracks), release internal self-healing agents, fill the damaged area, significantly extend the service life of the material, and reduce maintenance work. When the ambient temperature changes or the temperature inside the material rises to a certain level, the temperature-triggered microcapsules rupture or increase in permeability, releasing self-healing agents, which also help repair material deformation or damage caused by temperature. The combination of mechanical stress triggering and temperature triggering enables the material to respond automatically under a variety of environmental conditions, improving the adaptability of the material in a dynamic environment. The present invention customizes the microcapsules to suit specific applications and adjusts the reaction conditions (such as temperature, time, emulsifier and cross-linker concentrations) to achieve customization of the microcapsule properties to adapt to different mechanical or thermal environments.
[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A solid damping material for a passive tension-viscous damper, characterized in that: The solid damping material for the passive tension viscous damper includes the following components in mass fraction: 60-70 parts of polymer matrix; 8-12 parts of reinforcement material; 3-5 parts of plasticizer; 1-2 parts of cross-linking agent; 5-10 parts of microencapsulated self-healing agent; 3-8 parts of modified nano clay.
2. The solid damping material for a passive tension-viscous damper according to claim 1, characterized in that: The polymer matrix includes at least one of thermoplastic polyurethane elastomer, polyvinyl acetal, thermoplastic rubber, ethylene-vinyl acetate copolymer, silicone rubber, polycarbonate and epoxy resin.
3. The solid damping material for a passive tension-viscous damper according to claim 2, characterized in that: The reinforcing material comprises carbon nanotubes and graphene oxide, and the ratio of the carbon nanotubes to the graphene oxide is in the range of 2:1-3:
1.
4. The solid damping material for a passive tension-viscous damper according to claim 3, characterized in that: The plasticizer includes at least one of di(2-ethylhexyl)phthalate, diisononyl phthalate, dicyclohexyl phthalate, acetyl tributyl citrate and dioctyl adipate.
5. The solid damping material for a passive tension-viscous damper according to claim 4, characterized in that: The cross-linking agent includes at least one of dicumyl peroxide, benzoyl peroxide and azobisisobutyronitrile.
6. The solid damping material for a passive tension-viscous damper according to claim 5, characterized in that: The microencapsulated self-repairing agent is used to be distributed in the damping material matrix and trigger the self-repairing process of the solid damping material under different working conditions; The preparation of the microencapsulated self-repairing agent comprises: A self-healing agent is prepared, and a microcapsule wall material is selected according to the chemical properties of the self-healing agent and the expected triggering mechanism, wherein the self-healing agent includes epoxy resin and polyurethane, and the microcapsule wall material includes a mechanical stress-triggered microcapsule wall material and a temperature-triggered microcapsule wall material; The mechanical stress-triggered microcapsule wall material and the temperature-triggered microcapsule wall material are respectively stirred with the self-healing agent, and an emulsifier is added to form a corresponding mixed emulsion; Adding a microcapsule wall material crosslinking agent into the mixed emulsion allows the microcapsule wall material to polymerize at the emulsion interface to form a microcapsule shell layer. By controlling the key variables of the interfacial polymerization reaction, the desired microcapsule thickness and strength can be obtained. Stop the reaction, filter, wash and dry the microcapsules to obtain corresponding mechanical stress-triggered microcapsules and temperature-triggered microcapsules; Wherein, the mechanical stress-triggered microcapsule wall material comprises at least one of a brittle polymer and a polyacrylate; The temperature-triggered microcapsule wall material includes at least one of a thermosensitive polymer, a thermoplastic polymer and paraffin.
7. The solid damping material for a passive tension-viscous damper according to claim 6, characterized in that: The key variables for controlling the interfacial polymerization reaction to obtain the desired microcapsule thickness and strength include: Determine the key variables that affect microcapsule formation, including reaction temperature, reaction time, microcapsule wall material crosslinking agent concentration, emulsifier concentration, and stirring speed; The chemical reaction and material transfer in the interfacial polymerization process are simulated by modeling; the reaction conditions are optimized using numerical optimization techniques to find the optimal key variables; According to the optimization results, the key variables of the required microcapsule thickness and strength are obtained, and based on the key variables of the required microcapsule thickness and strength, the interfacial polymerization reaction of the microcapsule shell is realized to obtain the required microcapsule thickness and strength.
8. The solid damping material for a passive tension-viscous damper according to claim 7, characterized in that: The preparation of the modified nanoclay comprises: The nanoclay is purified by washing and centrifugation, and responsive functional groups are introduced into the surface of the nanoclay by chemical grafting, wherein the responsive functional groups include thermosensitive groups, pH-sensitive groups and photosensitive groups; Intercalants are used to adjust the interlayer spacing of nanoclay; pre-designed templates are used to guide the arrangement of nanoclay particles, and directional distribution of nanoclay is achieved through layer-by-layer self-assembly technology.
9. The solid damping material for a passive tension-viscous damper according to claim 8, characterized in that: The step of introducing responsive functional groups into the surface of nanoclay comprises: Prepare monomers containing thermosensitive groups, monomers containing pH-sensitive groups, monomers containing photosensitive groups and free radical initiators; Nanoclay, a monomer containing a thermosensitive group, a monomer containing a pH-sensitive group, a monomer containing a photosensitive group, and a free radical initiator are mixed in a reaction system; The polymerization reaction is initiated by heating the reaction system to obtain nano clay grafted with responsive functional groups.
10. A method for preparing a solid damping material for a passive tension viscous damper, characterized in that: The preparation method of the solid damping material for the passive tension viscous damper according to claim 9 comprises the following steps: Weighing various raw materials according to the proportions to obtain a polymer matrix, a reinforcing material, a plasticizer, a cross-linking agent, a microencapsulated self-healing agent and modified nanoclay; The modified nanoclay is dispersed in a solvent, and the modified nanoclay is dispersed using ultrasonic technology to obtain a nanoclay solution; the nanoclay solution is mixed with a polymer matrix solution, and the solvent is evaporated after stirring to obtain an intercalated composite material; Taking part of the intercalation composite material, adding part of the reinforcing material, the plasticizer, the cross-linking agent and all of the mechanical stress-triggered microcapsules, and mixing them using a high shear mixer to obtain a solid damping outer layer material; Taking another part of the intercalation composite material, adding another part of the reinforcing material, the plasticizer, the cross-linking agent and all the temperature-triggered microcapsules, and mixing them using a high shear mixer to obtain a solid damping inner layer material; The solid damping inner layer material is placed in a mold and pressed into shape; the solid damping outer layer material is covered on the solid damping inner layer material, pressed into shape again, and after curing treatment, a solid damping material is obtained.
Citation Information
Patent Citations
Self-repairing fiber reinforced polymer matrix composite and preparation method thereof
CN101629024A
High-performance damping material for support, preparation method and rubber damping support applying high-performance damping material
CN109233015A
High-damping oil-resistant damping rubber for electric reactor and preparation method of high-damping oil-resistant damping rubber
CN118638356A
Preparation method of polymer / layered silicale nano in tercalation composite material
CN1475509A
Liquid-retaining elastomeric compositions, process of preparation and uses thereof
US20200123338A1